2002
DOI: 10.1093/ndt/17.12.2170
|View full text |Cite
|
Sign up to set email alerts
|

Haemodialysis increases QTc interval but not QTc dispersion in ESRD patients without manifest cardiac disease

Abstract: Haemodialysis increases the QTc interval in ESRD patients, mainly related to rapid changes in electrolyte plasma concentrations. However, the impact on QTc dispersion is less important in the absence of significant coexisting cardiac disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
70
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 0 publications
13
70
1
1
Order By: Relevance
“…28 Electrocardiogram data demonstrate that the risk of arrhythmia could be higher with decreased plasma Na, K, and decreased ionized Ca during HD. 29 A study showed that hemodialysis increases the QTc interval in ESRD patients, mainly because of rapid changes in plasma electrolyte concentrations 16,30 ; another study indicated that there was no correlation between the changes in QTd and the changes in serum cations. However, the change in QTc correlated inversely with the change in serum calcium level.…”
Section: Discussionmentioning
confidence: 99%
“…28 Electrocardiogram data demonstrate that the risk of arrhythmia could be higher with decreased plasma Na, K, and decreased ionized Ca during HD. 29 A study showed that hemodialysis increases the QTc interval in ESRD patients, mainly because of rapid changes in plasma electrolyte concentrations 16,30 ; another study indicated that there was no correlation between the changes in QTd and the changes in serum cations. However, the change in QTc correlated inversely with the change in serum calcium level.…”
Section: Discussionmentioning
confidence: 99%
“…27 Prior reports have attributed these abnormalities to the high prevalence of LVH and electrolyte imbalance, 21 while others have suggested that they could be related to dialysis, because the QTc has been shown to prolong after dialysis. 28,29 None of these reports have accounted for the presence and/or severity of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Although ECGs are extensively used diagnostic tools, appropriate systematic evaluations regarding the prognostic utility in hemodialysis patients are absent. This is of particular importance, since in this high-risk group ECG interpretation might be compromised by the fact that volume and electrolyte status can influence various ECG variables like the QRS complex, QT interval and P-wave (3,4,5,6).…”
mentioning
confidence: 99%